1998
DOI: 10.1021/jo972057i
|View full text |Cite
|
Sign up to set email alerts
|

Oxysulfur Compounds Derived from Dimethyl Disulfide:  An ab Initio Study

Abstract: The optimized geometries of oxysulfur compounds derived from dimethyl disulfide were calculated at the MP2/6-31G* level, and the relative energies of isomers in the CH 3 S 2 OCH 3 , CH 3 S 2 O 2 CH 3 , CH 3 S 2 O 3 CH 3 , and CH 3 S 2 O 4 CH 3 series were compared. All these derivatives are characterized by long S-S bonds or long sulfenyl or sulfinyl S-O bonds for sulfur-oxygen-bridged isomers. According to the geometrical parameters calculated for vic-disulfoxide 4RR in the CH 3 S 2 O 2 CH 3 series, this comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 61 publications
4
21
0
Order By: Relevance
“…CH 3 S͑O͒OSCH 3 might be produced from reactions of CH 3 SO+ CH 3 SO or CH 3 SOO+ CH 3 S. Lacombe et al 64 also demonstrated that the self-reaction of CH 3 SO might produce CH 3 S͑O͒OSCH 3 and CH 3 S͑O͒S͑O͒CH 3 , CH 3 SO + CH 3 SO → CH 3 S͑O͒OSCH 3 ͑8͒ ⌬H = − 68 kJ mol −1 , The two additional intense bands of CH 3 S͑O͒OSCH 3 are predicted at 759 and 623 cm −1 , beyond our detection limit.…”
Section: E Possible Assignments Of Features E "è1170 CM −1mentioning
confidence: 99%
“…CH 3 S͑O͒OSCH 3 might be produced from reactions of CH 3 SO+ CH 3 SO or CH 3 SOO+ CH 3 S. Lacombe et al 64 also demonstrated that the self-reaction of CH 3 SO might produce CH 3 S͑O͒OSCH 3 and CH 3 S͑O͒S͑O͒CH 3 , CH 3 SO + CH 3 SO → CH 3 S͑O͒OSCH 3 ͑8͒ ⌬H = − 68 kJ mol −1 , The two additional intense bands of CH 3 S͑O͒OSCH 3 are predicted at 759 and 623 cm −1 , beyond our detection limit.…”
Section: E Possible Assignments Of Features E "è1170 CM −1mentioning
confidence: 99%
“…Complex 2 contains new oxysulfide species O 2 SOSO with an oxo bridge between the two S atoms: S1 has two terminal O atoms, while S2 has only one terminal O atom and is asymmetric (Figure 1, right). The O 2 SOSO type of oxysulfur and oxysulfide compounds is unknown to date but has been theoretically calculated [13] . The bridging S1ÀO5 and S2ÀO5 bonds in 2 differ significantly in length (S1ÀO5 1.709(5), S2ÀO5 1.636(6) ), and the latter has double-bond character.…”
mentioning
confidence: 99%
“…The m-O 2 SSO 2 ligand in 1 has a weak S À S bond of 2.330(2) . The O 2 SOSO type of oxysulfur and oxysulfide compounds is unknown to date but has been theoretically calculated [13] . Complex 2 contains new oxysulfide species O 2 SOSO with an oxo bridge between the two S atoms: S1 has two terminal O atoms, while S2 has only one terminal O atom and is asymmetric (Figure 1, right).…”
mentioning
confidence: 99%